Caracterización de la gestión universitaria dentro de la Universidad Laica Eloy Alfaro de Manabí (ULEAM), Ecuador - Quijije Alvarado, Jahaira (2019)
This article focuses on one of the most significant problems of higher education in Ecuador: university management. Its definition is the only element designed with an academic perspective, since administrative actions have not been included and there is a lack of information regarding its components, without which no examination or characterization is possible. As a result, this study analyzes and describes management at the Universidad Laica Eloy Alfaro de Manabí (ULEAM) via the implementation of “Dimensión II. Misión y proyecto institucional. Gobierno y gestión” [Dimension II. Institutional mission and project. Government and management], which integrates the tool used by the Comisión Nacional de Evaluación y Acreditación Universitaria [National Commission for University Evaluation and Accreditation] (CONEAU) of Argentina in their evaluation processes. This tool has been adapted to the Likert scale survey in order to collect data gathered from faculty and non-faculty members. Finally, the results showed a serious weakness in government, management and governability factors.